Characterization of Diarrhetic Shellfish Toxins in the Mizuhopecten yessoensis (Scallop) Midgut Gland by High-Performance Liquid Chromatography – Tandem Mass Spectrometry (HPLC-MS/MS). (4th March 2023) - Yarita, Takashi; Inagaki, Shinsuke
Abstract: Liquid chromatography – tandem mass spectrometry (LC-MS/MS) is routinely applied for the determination of toxins associated with diarrhetic shellfish poisoning (DSP) as a part of the Japanese official method. For scallops, not only the edible part but also the midgut gland may be used for analysis. In this study, the matrix effects in the LC-MS/MS-based determination of okadaic acid (OA) and dinophysistoxin-1 (DTX1) in the scallop midgut gland were evaluated to assess the impact on the accuracy of the results. The analyzed sample in an interlaboratory comparison study was subjected to the Japanese official method. The solutions obtained with and without a cleanup process (combination of hexane washing and solid-phase extraction using a C18 cartridge) were diluted to varying ratios and used for evaluation. For all prepared solutions, the ionization of OA and DTX1 was enhanced compared to the samples in methanol; the cleanup process did not sufficiently reduce the matrix effects. Although the dilution of the sample solution reduced the matrix effect, the improvement was limited. Another pretreatment technique is necessary for the accurate determination of DSP-associated toxins in this matrix.